2008
DOI: 10.1039/b812536h
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic reactions: effects of ball milling, microwave and ultrasound irradiation

Abstract: Ball milling, microwave heating and ultrasound irradiation can be used to support conventional laboratory techniques. By applying them, a number of organocatalytic processes could be improved and superior results have been achieved compared to reactions performed under standard conditions. The purpose of this overview is to highlight recent advances by presenting selected examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
136
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(140 citation statements)
references
References 80 publications
0
136
0
4
Order By: Relevance
“…4 In the context of organic synthesis, mechanochemistry has been demonstrated to provide a solvent-free path to a plethora of transformations, including oxidations, 5 reductions, 6 Wittig condensations, 7 palladium-catalyzed Sonogashira 8 and Suzuki couplings. 9 Recently, different research groups including Ondruschka and co-workers 10 and Bolm and co-workers, 11 have demonstrated that besides allowing solvent-free reactivity mechanochemical synthesis in a planetary mill allows substantial improvements in energy efficiency, compared to conventional solutionbased or microwave-assisted synthesis.…”
Section: Mechanosynthesis In Organic Synthesis and Cocrystallizationmentioning
confidence: 99%
“…4 In the context of organic synthesis, mechanochemistry has been demonstrated to provide a solvent-free path to a plethora of transformations, including oxidations, 5 reductions, 6 Wittig condensations, 7 palladium-catalyzed Sonogashira 8 and Suzuki couplings. 9 Recently, different research groups including Ondruschka and co-workers 10 and Bolm and co-workers, 11 have demonstrated that besides allowing solvent-free reactivity mechanochemical synthesis in a planetary mill allows substantial improvements in energy efficiency, compared to conventional solutionbased or microwave-assisted synthesis.…”
Section: Mechanosynthesis In Organic Synthesis and Cocrystallizationmentioning
confidence: 99%
“…[15][16][17][18][19][20] In continuation of our previous work to discover new bioactive heterocyclic compounds, [21][22][23][24][25][26][27][28][29][30][31] we aimed here to synthesize new pyrazolyl-azolopyrimidines via ecofriendly method to evaluate their antibacterial activity.…”
mentioning
confidence: 99%
“…7,[10][11][12] A organocatálise assimétrica vem apresentando um impacto significativo em síntese orgânica na última década, como ferramenta para a preparação de blocos de construção quirais e ingredientes farmacologicamente ativos. [13][14][15][16] Além da reconhecida eficiência catalítica, organocatalisadores possuem diversas vantagens em relação aos complexos de metais de transição tradicionalmente empregados em síntese assimétrica, incluindo maior estabilidade, facilidade de acesso e menor custo. Portanto, este é um tópico que deve estar presente nos conteúdos programáticos de disciplinas de Química Orgânica.…”
Section: Introductionunclassified